2022
DOI: 10.1007/s00421-022-04948-w
|View full text |Cite
|
Sign up to set email alerts
|

Maximal strength training in patients with inflammatory rheumatic disease: implications for physical function and quality of life

Abstract: Purpose Patients with inflammatory rheumatic disease (IRD) have attenuated muscle strength in the lower extremities, resulting in impaired physical function and quality of life. Although maximal strength training (MST), applying heavy resistance, is documented to be a potent countermeasure for such attenuation, it is uncertain if it is feasible in IRD given the pain, stiffness, and joint swelling that characterize the population. Methods 23 patients with I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 51 publications
3
3
0
Order By: Relevance
“…This study's 16‐week SDT‐based physical activity programme showed that the intervention group improved more in psychosocial aspects than the control group, specifically regarding the HRQoL and physical indicators. This finding is consistent with a previous RCT that investigated the effects of maximal strength training in patients with inflammatory rheumatic diseases (Haglo et al, 2022), showing that the intervention significantly improved the participants' physical functioning as well as HRQoL. Perceived change in the quality of life is an important factor in maintaining the physical activity of a health intervention (Salemonsen et al, 2018); thus, future physical activity intervention studies must incorporate methods for improving psychosocial factors as well as promoting physical activity in individuals with RA.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study's 16‐week SDT‐based physical activity programme showed that the intervention group improved more in psychosocial aspects than the control group, specifically regarding the HRQoL and physical indicators. This finding is consistent with a previous RCT that investigated the effects of maximal strength training in patients with inflammatory rheumatic diseases (Haglo et al, 2022), showing that the intervention significantly improved the participants' physical functioning as well as HRQoL. Perceived change in the quality of life is an important factor in maintaining the physical activity of a health intervention (Salemonsen et al, 2018); thus, future physical activity intervention studies must incorporate methods for improving psychosocial factors as well as promoting physical activity in individuals with RA.…”
Section: Discussionsupporting
confidence: 93%
“…This study's 16-week SDT-based physical activity programme showed that the intervention group improved more in psychosocial aspects than the control group, specifically regarding the HRQoL and physical indicators. This finding is consistent with a previous RCT that investigated the effects of maximal strength training in patients with inflammatory rheumatic diseases (Haglo et al, 2022), showing that the intervention significantly improved the participants' physical T A B L E 3 Group-by-time effects of the programme using repeated measures analysis of variance. (Fenton et al, 2021).…”
Section: Ancillary Analyses: Effects On Sdt-related Variablessupporting
confidence: 90%
“…This is in accordance with our hypothesis and several studies describing their experimental group as "high-intensity" (Cerini et al, 2022;Verbrugghe et al, 2019). In fact, recent studies in patients with inflammatory rheumatic disease, which, in a similar fashion to the current study population, are characterized by pain and stiffness, also reported that high-intensity training was feasible (Haglo et al, 2021(Haglo et al, , 2022. These observations contrast a recent meta-analysis that reported an increased dropout from highintensity compared to lower-intensity exercise in patients with fibromyalgia (Vancampfort et al, 2023)…”
Section: The Feasibility Of High-intensity Exercise For Patients With...supporting
confidence: 93%
“…The strength training in the horizontal leg press consisted of 4 sets of 4 repetitions at ∼90% of 1RM and is referred to as maximal strength training; MST. Emphasis was placed on maximal intended velocity and mobilization in the concentric phase (Behm et al., 1993), and the eccentric phase was performed with relatively slow velocity to minimize eccentric forces (Haglo et al., 2022). When a patient was able to conduct more than four repetitions in the last set, the load was increased by 4.5 kg in the following session.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation